(untitled) (Web of Teachers: Inderscience Research, 2025)
This paper examines the role of Russian folk tales as an effective means of familiarising junior schoolchildren with the culture and traditions of the Russian people. The peculiarities of folk tales that help to convey historical and cultural values, plot structures and characters representing national archetypes are analysed. Special attention is paid to the methods of teachers’ work with Russian folk tales in literature lessons and extracurricular activities, as well as to the ways in which fairy tales contribute to the formation of children’s interest in their culture and the development of their aesthetic perception. The study emphasises the importance of integrating folklore into the educational process in order to foster patriotism, respect for historical heritage and develop moral qualities in children.